Utilização e gestão de laboratórios escolares - Santana, Salete de Lourdes Cardoso (2011)
The scenario of Brazilian education has been improving year on year, according to official figures. However, with regard to the teaching of science and practical classes, especially in public schools, there is still a long way to go. In view of this, and seeking help to illustrate the current state of public schools regarding the existence and use of school laboratories, whether in science or computer, we proposed that this work aims to: make a diagnosis of the situation of public schools elementary schools in the cities of Barra do Quaraí and Uruguaiana located on the western border of Rio Grande do Sul, in relation to the presence and use of school laboratories, both computer science and propose the effective use of space, especially the science lab, suggesting appropriate management techniques and waste treatment practices from lessons and suggest the implementation of a project for a science lab in the School Hall Elementary School October 22, located in Barra do Quaraí. To perform the first phase were carried out visits to 35 schools, state and municipal, urban and rural areas. During his visit to the 1430 questionnaire were applied students, 46 teachers and 37 administrators. Of all the schools surveyed, was found the following situation: have 16 science lab and computer lab are 34 (only one state school does not have either). Where permitted, the spaces were visited in order to see the facilities and infrastructure. With the data collected it was possible to detect positive and negative aspects of the use or nonuse of the laboratories for each category, as well as evaluating the importance of these activities and these spaces represent the school life of students and the group of teachers and administrators. These data served as a basis for the production of the second phase, which was the production of two booklets, one containing the proposal and suggested the use of experimental activities and the other dealing with the issue of waste and safety when conducting the practical classes. The third phase involved the preparation of the proposed deployment of the laboratory. The data analysis, and result in a manuscript, also allowed to profile all those involved in research as well as the vision of the same when it comes to practical classes. Thus, the booklets are a way to encourage the use of laboratories and assist teachers in planning classroom practices. Also, addressing the issue of waste, we seek to answer questions about the proper disposal of waste and waste resulting from the experimental activities. Each of the materials produced with this work counts as a contribution and response to each school that agreed to participate.